Mobile health clinics for distribution of vaccinations to underserved communities during health emergencies: A COVID-19 case study - Lior Rennert; Fatih Gezer; Iromi Jayawardena; Kerry A. Howard; Kevin J. Bennett; Alain H. Litwin; Kerry K. Sease (Elsevier, 2024)
Objectives: Mobile health clinics (MHCs) effectively provide healthcare to underserved communities. However, their application during health emergencies is understudied. We described the implementation of an MHC program delivering vaccinations during the COVID-19 pandemic, examined the program's reach to medically underserved communities, and investigated characteristics of vaccination uptake in order to inform the utility of MHCs during health emergencies. Study design: The study observed COVID-19 MHC vaccination rates and factors associated with uptake between February 20th, 2021, and February 17th, 2022. Methods: Prisma Health deployed six MHCs to underserved communities. We described the characteristics of individuals who utilized the MHCs and evaluated census tract-level community factors associated with use of the MHCs through generalized linear mixed effects models. Results: The MHCs conducted 260 visits at 149 unique sites in South Carolina, providing 12,102 vaccine doses to 8545 individuals: 2890 received a partial dose, 4355 received a primary series, and 1300 received a booster dose. Among individuals utilizing the MHC, the median age was 42 years (IQR: 22-58), 44.0 % were Black, 49.2 % were male, and 44.2 % were uninsured. Black, Hispanic, and uninsured individuals were significantly more likely to utilize MHC services for COVID-19 vaccination. During periods when vaccines were limited, MHC utilization was significantly greater in communities facing access barriers to healthcare. Conclusions: The high COVID-19 vaccination uptake at MHCs demonstrated that the MHC framework is an effective and acceptable intervention among medically underserved populations during health emergencies, especially when resources are scarce. The identified factors associated with vaccination uptake demonstrated that the MHCs had the greatest impact in higher-risk communities and can be used to inform allocation of such field-level interventions in future health emergencies.